ENTORNO FAMILIAR Y SU INFLUENCIA EN EL PROCESO DE ENSEÑANZA – APRENDIZAJE EN ESTUDIANTES DEL 4TO CURSO DE LA UNIDAD EDUCATIVA EMIGDIO ESPARZA MORENO - MACIAS MAYORGA JOAN ARIEL (2024)
The project focuses on the relationship between the family environment and the academic performance of fourth-year students at the Emigdio Esparza Moreno Educational Unit. Through a mixed methodology that integrates qualitative and quantitative analysis, it examines how family dynamics and conditions affect education. It identifies key factors such as emotional support, communication, and participation in educational activities, highlighting their impact on students' motivation and learning. The study proposes interventions to strengthen collaboration between the school and families, emphasizing the importance of an educational approach that considers the family context to improve academic outcomes. Furthermore, it suggests the need for inclusive educational policies that facilitate the active participation of parents and guardians in the educational process, promoting an environment conducive to the comprehensive development of students